Nonprofessional involvement in helping services in Palmerston North : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Daniels, Kenneth Raymond (Massey University, 1974)
Helping as it has been influenced by the development of a welfare state philosophy is examined. A review is made of the societal changes that have and are continuing to have a potent influence on the established networks of support, care and help. The results of these societal changes and consequent network changes are seen in the rapid increase in demands for professional helping services. These rapidly increased demands have been matched by a rapid increase in personnel in helping services. The contribution of the nonprofessional has been somewhat curtailed as a result of the emphasis on the growth of professional helpers. The literature from overseas records evidence of the re-emergence of the nonprofessional helper as a powerful contributor to meeting the needs of the community. In this respect the concept of 'community care' is becoming a reality. The literature reviewed points to the contribution the nonprofessional is and can be making and overwhelmingly supports the positive nature of this contribution. This study examined what happened in Palmerston North in terms of the nonprofessional contribution to helping services. All professional helpers (psychiatrists, psychologists, counsellors and social workers) in the city, were interviewed and a 20% sample of nonprofessional helpers drawn from selected helping agencies were interviewed. 75 professional helpers and 76 nonprofessional helpers were interviewed personally, two separate questionnaires being used. The results show that helpers were predominantly aged 31 to 60 (75%) and less than 2% were under 22. There were equal numbers of males and females. 81.4% of professional helpers worked in government or quasi-government services, while only 3.9% of nonprofessionals linked up with such services to make their contributions. Over half of the professional helpers are social workers and only 40% of all professional helpers have a professional qualification. Both professional and nonprofessional helpers feel overwhelmingly that the nonprofessional has a contribution to make. However 56.6% of nonprofessionals had never been asked for help by a professional. Those who had been asked, were most frequently asked to provide 'befriending/support'. This is what most nonprofessionals wanted to be asked to do and over half of the professionals felt this was the best contribution the nonprofessional could make. Almost 100% of nonprofessionals felt capable of offering 'material' help or 'befriending/support', while 77% felt capable of offering 'advice and guidance' and 51% 'counselling'. 42.6% of professionals had requested nonprofessional assistance in the past week, while 7.9% of nonprofessionals had received such a request in the same period. Overall, nonprofessionals felt that professionals understood them, but almost 20% felt they did not receive enough encouragement or support. The expectations each group had of the other were investigated and it was found that overall, both groups had similar expectations. The advantages and disadvantages each group had found of working with the other were explored. The results give a valuable insight into the positive and negative experiences helpers in each group have had of working with the other group. Three implications are drawn from the study, firstly concerning the utilization of resources, secondly, relationship factors and thirdly, differentiation of skills.
Keywords: New Zealand; Palmerston North; Social service; Public welfare